Growth responses and ion accumulation in the halophytic legume Prosopis strombulifera are determined by Na2SO4 and NaCl - Reginato, Mariana Andrea (2014)
Halophytes are potential gene sources for genetic manipulation of economically important crop species. This study addresses the physiological responses of a widespread halophyte, Prosopis strombulifera (Lam.) Benth to salinity. We hypothesised that increasing concentrations of the two major salts present in soils of central Argentina (Na2SO4, NaCl, or their iso-osmotic mixture) would produce distinct physiological responses. We used hydroponically grown P. strombulifera to test this hypothesis, analysing growth parameters, water relations, photosynthetic pigments, cations and anions. These plants showed a halophytic response to NaCl, but strong general inhibition of growth in response to iso-osmotic solutions containing Na2SO4. The explanation for the adaptive success of P. strombulifera in high NaCl conditions seems to be related to a delicate balance between Na+ accumulation (and its use for osmotic adjustment) and efficient compartmentalisation in vacuoles, the ability of the whole plant to ensure sufficient K+ supply by maintaining high K+/Na+ discrimination, and maintenance of normal Ca2+ levels in leaves. The three salt treatments had different effects on the accumulation of ions. Findings in bi-saline-treated plants were of particular interest, where most of the physiological parameters studied showed partial alleviation of SO42−-induced toxicity by Cl−. Thus, discussions on physiological responses to salinity could be further expanded in a way that more closely mimics natural salt environments.